2022
DOI: 10.3390/molecules27227994
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Breast Cancer Activity of Dihydroartemisinin-5-methylisatin Hybrids Tethered via Different Carbon Spacers

Abstract: Sixteen dihydroartemisinin-5-methylisatin hybrids 6a–c and 7a–m tethered via different carbon spacers were assessed for their antiproliferative activity against MCF-7, MDA-MB-231, MCF-7/ADR and MDA-MB-231/ADR breast cancer cell lines as well as cytotoxicity towards MCF-10A cells to investigate the influence of the length of carbon spacers on the activity. The preliminary results illustrated that the length of the carbon spacer was the main parameter which affected the activity, and hybrids tethered via the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Cao et al reported [ 86 , 87 ] a series of dihydroartemisinin–isatin hybrids conjugated through a nucleophilic substitution by reacting a series of tosylate derivatives of dihydroartemisinin ( 2 ) with isatin derivatives substituted at C-3 with different groups such as methoxy, fluorine and methyl. The synthesis of the most potent hybrids of the series is reported in Scheme 27 .…”
Section: Artemisinin Hybrids Based On Natural and Synthetic Pharmacop...mentioning
confidence: 99%
See 2 more Smart Citations
“…Cao et al reported [ 86 , 87 ] a series of dihydroartemisinin–isatin hybrids conjugated through a nucleophilic substitution by reacting a series of tosylate derivatives of dihydroartemisinin ( 2 ) with isatin derivatives substituted at C-3 with different groups such as methoxy, fluorine and methyl. The synthesis of the most potent hybrids of the series is reported in Scheme 27 .…”
Section: Artemisinin Hybrids Based On Natural and Synthetic Pharmacop...mentioning
confidence: 99%
“…The synthesis of the most potent hybrids of the series is reported in Scheme 27 . The new hybrids 149a [ 86 ] and 149b [ 87 ] presented alkyl chains of different lengths and different substituents at the C-5 position of the isatin moiety. Hybrids 149a and 149b were in turn modified at the C-3 position of the isatin moiety with, among others, hydroxime and thiosemicarbazide moieties, leading to hybrids 150a and 150b , respectively.…”
Section: Artemisinin Hybrids Based On Natural and Synthetic Pharmacop...mentioning
confidence: 99%
See 1 more Smart Citation
“…A significant part of alkyl tethered isatin-dihydroartemisinin hybrids 6 (Figure 3; IC 50 : 18.9-88.3 µM) were active against MDA-MB-231, MCF-7, and their multidrug-resistant counterparts MCF-7/ ADR as well as MDA-MB-231/ADR BC cell lines, and the activity was better compared with that of artemisinin (IC 50 : 72.4->100 µM) and dihydroartemisinin (IC 50 : 69.6-82.8 µM). [29,30] The SARs illustrated that (1) the activity was increased by extending the carbon spacer between the isatin and dihydroartemisinin motifs; (2) the activity benefited from the presence of hydrogen bond donors like thiosemicarbazide and oxime at the C-3 position and fluorine at the C-5 position of the isatin skeleton. In particular, hybrids 6a-c (IC 50 :…”
Section: Isatin-dihydroartemisinin Hybridsmentioning
confidence: 99%
“…A significant part of alkyl tethered isatin‐dihydroartemisinin hybrids 6 (Figure 3; IC 50 : 18.9–88.3 µM) were active against MDA‐MB‐231, MCF‐7, and their multidrug‐resistant counterparts MCF‐7/ADR as well as MDA‐MB‐231/ADR BC cell lines, and the activity was better compared with that of artemisinin (IC 50 : 72.4–>100 µM) and dihydroartemisinin (IC 50 : 69.6–82.8 µM). [ 29,30 ] The SARs illustrated that (1) the activity was increased by extending the carbon spacer between the isatin and dihydroartemisinin motifs; (2) the activity benefited from the presence of hydrogen bond donors like thiosemicarbazide and oxime at the C‐3 position and fluorine at the C‐5 position of the isatin skeleton. In particular, hybrids 6a–c (IC 50 : 15.1–18.3, 15.3–20.1, and 18.9–26.6 µM, respectively) were comparable to doxorubicin (IC 50 : 18.9 µM) against MCF‐7 cancer cells and >3.7 times more potent than doxorubicin (IC 50 : >100 µM) against multidrug‐resistant MCF‐7/ADR and MDA‐MB‐231/ADR BC cell lines, highlighting their ability to overcome drug resistance.…”
Section: Isatin‐dihydroartemisinin Hybridsmentioning
confidence: 99%